161 Cross Sectional Study of Pharmacological Management of Rheumatoid Arthritis in Patients over the age of 70. (16th September 2019) - Reddin, Catriona; Costello, Maria; Lynch, Bernadette
Abstract: Background: Rheumatoid arthritis (RA) is a common inflammatory joint disease. It can lead to joint destruction resulting in joint deformity, functional impairment and reduced mobility. With a growing older population, prevalence of RA is increasing and due to the associated morbidity it is essential to prioritise disease control. Conventional treatment of RA has comprised of disease modifying anti rheumatic drugs (DMARDs) along with analgesia and corticosteroids. Recently, the development of biologics has revolutionised management of inflammatory arthritis. We now strive for tighter control to prevent joint damage and preserve function. However, studies have shown that uptake of biologic medications in the older population has been slower than their younger counterparts. (1) Methods: Our departmental electronic record system, Cellma, was interrogated for patients aged 70 and over with a diagnosis of RA. Deceased patients were excluded. The current medication list was reviewed using the online rheumatology outpatient system. Results: A total of 514 patients over the age of 70 were identified with a diagnosis of RA [(67% (n=343) female, 33% (n=171) male)], 24.5% (n=126) were on biologic therapy, 13% (n=68) patients were on a single DMARD in combination with a biologic, 42% (n=217) of patients were on a single conventional DMARD alone and 9.7% (n=50) were on analgesia alone. Conclusion: The management of RA in the older population poses its own challenges but this should not prohibit the thoughtful use of newer agents. Awareness of the therapeutic potential and associated adverse events is necessary for maximizing therapeutic benefits while minimizing adverse effects from conventional DMARDs and biologic therapies.